2007
DOI: 10.1007/s00420-007-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Korean version of the effort–reward imbalance questionnaire: a study in a petrochemical company

Abstract: These findings contribute to the validity and reliability of the Korean ERI questionnaire. Importantly, in the context of a rapid change in the labour market, the lack of reciprocity between efforts and rewards at work is strongly associated with self-rated physical and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
4
32
4
3
Order By: Relevance
“…Similar to that found on petrochemical industry workers in Korea (Eum et al, 2006) and in Chinese health care workers (Li, Yang, & Cheng, 2005). The results confirmed the hypothesis of Li et al (2005) who point out that there are cultural variations in the perception of stressful experience in the work.…”
Section: Psychometric Behavior Of the Short Version Of Effort-reward 217supporting
confidence: 79%
“…Similar to that found on petrochemical industry workers in Korea (Eum et al, 2006) and in Chinese health care workers (Li, Yang, & Cheng, 2005). The results confirmed the hypothesis of Li et al (2005) who point out that there are cultural variations in the perception of stressful experience in the work.…”
Section: Psychometric Behavior Of the Short Version Of Effort-reward 217supporting
confidence: 79%
“…Job stress, as the main psychological work-related disease in China, might lead to poor health and even injury, including cardiovascular diseases [9], MSDs [10], and mental illness [11]. A study in Chinese working women revealed that the combined exposure to job and family stress was associated with an adjusted mean 6.4 mmHg increase in systolic blood pressure [12].…”
Section: Other Occupational Health Problemsmentioning
confidence: 99%
“…Such findings would underline the evolutionary old 'grammar' of social exchange that may be rooted in distinct structures of the human brain (Cosmides and Tooby, 1992). Currently, a number of findings from observational studies confirm that effortreward imbalance at work is associated with elevated risks of stress-related disorders in Japanese (Tsutsumi et al, 2001), Chinese (Xu et al, 2004;Li et al, 2005), South Korean (Eum et al, 2007), Thay (Buapetch et al, 2008) and Brazilian (Chor et al, 2007) working populations, thus lending support to the idea that the experience of unfair exchange results in negative emotions and adverse well-being cross-culturally in similar ways. This discovery is of interest in view of the process of economic globalisation and associated trans-national labour market mobility.…”
Section: Brief Summary Of Empirical Evidence On Health-adverse Effectsmentioning
confidence: 86%